A four-step method for electric-vehicle charging facility deployment in a dense city: An empirical study in Singapore. (January 2019) - Wang, Hua; Zhao, De; Meng, Qiang; Ong, Ghim Ping; Lee, Der-Horng
Abstract: In the recent decade, electric vehicles (EVs), as a clean and cost-effective transport means, are paving the way to replace conventional gasoline vehicles. To facilitate wider adoption of EVs, corresponding charging infrastructures have to be established first. In this paper, we propose a four-step method to deploy normal and fast charging stations that can satisfy the charging demand of private EVs, 1-shift and 2-shift EV taxis in a mature city. The proposed four-step method provides an easy-to-implement procedure for charging demand estimation and distribution. First, we derive the charging frequency and type of charging facilities for each type of EVs based on their technical specifications and operational characteristics. Then, total demand for normal and fast charging facilities can be generated by using up-to-date transport statistics, and these demand is allocated to various charging sites (car parks or petrol stations) based on spatial distribution of EVs. Given the average daily engaged working hours of a charger, service capacity at each charging station is thus determined. A case study of Singapore is put forward in the end and a scenario analysis is conducted to demonstrate the impact of driving range.